Sex differences and mechanisms of muscle pain. - Queme, Luis F (Curr Opin Physiol, 2019)
Clinical conditions resulting in musculoskeletal pain show important sex differences in both prevalence and degree of functional disability. The underlying mechanisms for these distinctions in pain manifestation are not fully known. However, recent preclinical studies have shown at the primary afferent level that males and females present fundamental differences in their peripheral response properties and injury-related gene expression patterns that may underlie observed afferent sensitization. At the spinal cord level, studies in various models of pain suggest important roles for the immune system, glutamate signaling and hormones in modulating sex differences. While preclinical studies have been able to characterize some of the basic underlying molecular mechanisms of sex differences in muscle pain, human studies have relied mainly on functional brain imaging studies to explain differences. Further complicating our understanding of how sex influences muscle pain is the notion that the type of injury sustained, or clinical condition may differentially activate distinct mechanisms of muscle pain development in males versus females. More research is necessary to better understand how the sexes differ in their perception of muscle pain. This review highlights recent advances in both human and animal studies of sex differences in muscle pain.